Integration of Maqashid Sharia in the Recognition and Management of Fixed Assets of BAZNAS Tulungagung Regency - Pepen Tri Malaika Rizky; Sri Luayyi; Ahmad Yani (LP2M IAIN Palopo, 2026)
This study aims to analyze the integration of Maqāṣid al-Sharī‘ah values in the practice of recognition and management of fixed assets at BAZNAS Tulungagung Regency as a form of accountability in the management of zakat, infaq, and alms (ZIS) funds. The study employs a descriptive qualitative approach with data collection techniques including non-participant observation, in-depth interviews with key informants consisting of management and relevant staff, and documentation of the 2024 financial reports. Data analysis was conducted descriptively by comparing fixed asset recognition and management practices against operational indicators for each dimension of Maqāṣid al-Sharī‘ah. The findings show that fixed asset recognition is in accordance with nonprofit accounting practices, where donated assets are recognized at fair value at the time of acquisition, while assets obtained through murābaḥah are recorded at acquisition cost until they are ready for use. The straight-line depreciation policy and preventive maintenance are consistently applied as a form of asset value protection. The dominance of the ḥifẓ al-māl dimension is reflected in policies focusing on asset control, protection, and sustainability. Meanwhile, the ḥifẓ al-nafs dimension is reflected in the use of operational vehicles for aid distribution and social response activities, and the ḥifẓ al-ʿaql dimension is reflected in the use of information technology in data management and decision-making processes. The implications of this study indicate that Maqāṣid al-Sharī‘ah can be used as an evaluative framework in the management of fixed assets within zakat institutions. Practically, the findings may serve as a basis for developing maqāṣid-based asset management policies to enhance transparency, accountability, and public trust. This study also contributes novelty through an evaluative approach that systematically integrates fixed asset accounting practices with operational indicators of Maqāṣid al-Sharī‘ah in the context of local zakat institutions.